The Reproductive Toxicity of Monosodium Glutamate by Damaging GnRH Neurons Cannot Be Relieved Spontaneously Over Time - Wang CX; Zhang Y; Li QF; Sun HL; Chong HL; Jiang JX; Li QC (Dove Medical Press, 2021)
Cheng-Xiang Wang,1,* Yue Zhang,1,* Qing-Feng Li,2 Hong-Liang Sun,1 Hai-Ling Chong,1 Jian-Xi Jiang,1 Qing-Chun Li1 1Department of Reproductive Medicine, Binzhou Medical University Hospital, Binzhou, Shandong, People's Republic of China; 2Smart Gas Division, Qingdao iESLab Electronic Co., Ltd, Qingdao, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Qing-Chun LiDepartment of Reproductive Medicine, Binzhou Medical University Hospital, No. 661 Huanghe 2nd Road, Binzhou, 256603, People's Republic of ChinaTel +86 543 325 8715Fax +86 543 325 7792Email qingchunli_doc@163.comObjective: The present study aims to evaluate the effect of monosodium glutamate on testicular spermatogenesis in mice from the perspective of the hypothalamic-pituitary-testicular axis and whether this destructive effect is alleviated with time.Methods: Neonatal mice were randomly divided into a monosodium glutamate (MSG) group and a control group, just below the interscapular region after birth with 10 μL MSG to deliver 4 mg/g (body mass), or with equivalent volumes of 0.9% saline. Samples which involved blood, brains and testicles of mice were collected and measured at puberty at 60 days and adulthood at 90 days.Results: The results show that the fluorescence intensity of GnRH nerve fibers, the levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) hormones in the reproductive system, the number of spermatocytes and spermatozoa in testicular sections, the body length, body weight, testicular weight, and testicular index in the 60-day-old mice in monosodium glutamate group (MSG60 group) and the MSG90 group were lower than those in the 60-day-old mice in normal control group (NC60 group) (p < 0.05), but the number of apoptotic cells in the testicular section was higher than in the NC60 group (p < 0.05). When the 90-day-old mice in monosodium glutamate group (MSG90 group) was compared with the MSG60 group, except for body weight and testicular weight increase (p < 0.05), there is no significant difference in the other parameters mentioned above (p > 0.05).Conclusion: Monosodium glutamate can cause reproductive toxicity to male mice by damaging GnRH neurons, and this reproductive toxicity cannot be relieved spontaneously over time. These findings are supported by observed histological changes.Keywords: monosodium glutamate, neurotoxicity, GnRH neurons, reproductive organs